Caracterização do ciclo da marcha em amputado transtibial com prótese inteligente - Moreira, Fabiano Marques (2016)
This work presents an application of optical fiber sensors based on Bragg gratings integrated to a transtibial prosthesis tube manufactured with a polymeric composite systrem of epoxy resin reinforced with glass fiber. The main objective of this study is to characterize the sensors applied to the gait cycle and changes in the gravity center of a transtibial amputee, trough the analysis of deformation and strengh of the transtibial prosthesis tube. For this investigation it is produced a tube of the composite material described above using the molding method of resin transfer (RTM) with four optical sensors. The prosthesis in which the original tube is replaced is classified as endoskeletal, has vacuum fitting, aluminium conector tube and carbon fiber foot cushioning. The volunteer for the tests was a man of 41 years old, 1.65 meters tall, 72 kilograms and left-handed. His amputation occurred due to trauma (surgical section is in the medial level, and was made below the left lower limb knee). He has been a transtibial prosthesis user for two years and eight months. The characterization of the optical sensors and analysis of mechanical deformation and tube resistance occurred through the gait cycle and the variation of the center of gravity of the body by the following tests: stand up, support leg without the prosthesis, support in the leg with the prosthesis, walk forward and walk backward. Besides the characterization of optical sensors during the gait cycle and the variation of the gravity center in a transtibial amputated, the results also showed a high degree of integration of the sensors in the composite and a high mechanical strength of the material.